The Study of the Reservoir Inter-architecture Structure and Remaining Oil in the Eastern Part of Sabei Ⅱ District (Rudarsko-geološko-naftni zbornik, 2019)
In the Daqing oilfield,HeilongjiangProvince, China,in the eastern part of the Sabei Ⅱ District is a fine potential-tapping demonstration area with a long development time and complex history of well conditions. As oil exploration has entered into the high-water cut stage, the fine description of reservoir structure hada great significance to improve the effect of oil exploration. An abandoned channel is an important basis for recognizing a single river border and point bar. The top sand-shale interbedded or muddy sediments have a shelter action for the reservoir fluid, so correctly recognizing the abandoned channel is an important scientific basis for further analysing reservoir architecture and exploring the remaining oil. Due to the lateral shelter action of sand-shale interbedded with muddy sediments, the semi-connected body, consisting of abandoned and normal channel sand body, leads to an injection and production imbalance, which is namely production without injection or injection without production. It makes the top of the channel sand body become the favourable gathering place for remaining oil and a further main exploring object.